2021
DOI: 10.3390/ijms22126585
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Diversification, and Expression Analysis of Lectin Receptor-Like Kinase (LecRLK) Gene Family in Cucumber under Biotic Stress

Abstract: Members of the lectin receptor-like kinase (LecRLKs) family play a vital role in innate plant immunity. Few members of the LecRLKs family have been characterized in rice and Arabidopsis, respectively. However, little literature is available about LecRLKs and their role against fungal infection in cucumber. In this study, 60 putative cucumber LecRLK (CsLecRLK) proteins were identified using genome-wide analysis and further characterized into L-type LecRLKs (24) and G-type LecRLKs (36) based on domain compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…Similar motif patterns have been found in CslecRLKs of cucumber ( C. sativus ) and Cerasus humilis showing distinct motif features related to the variations in their protein sequences. In total, 10 conserved motifs were observed in CslecRLKs ranging from 4 to 10 in each protein and 14 conserved motifs in Cerasus humilis [ 84 , 85 ]. Motifs 1 to 5 were predominantly identified in L-type CsLecRLK, whereas motif 1, motif 2, motif 6, and motif 8 were frequently observed in G-type CsLecRLK protein [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar motif patterns have been found in CslecRLKs of cucumber ( C. sativus ) and Cerasus humilis showing distinct motif features related to the variations in their protein sequences. In total, 10 conserved motifs were observed in CslecRLKs ranging from 4 to 10 in each protein and 14 conserved motifs in Cerasus humilis [ 84 , 85 ]. Motifs 1 to 5 were predominantly identified in L-type CsLecRLK, whereas motif 1, motif 2, motif 6, and motif 8 were frequently observed in G-type CsLecRLK protein [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicated that SBP1 and SBP2 may specifically regulate RLP receptor‐mediated immune responses. Genome‐wide analysis from previous reports revealed that G‐type LecRLKs are widespread and conserved in many plant species including cucumber (Haider et al, 2021), tomato (Teixeira et al, 2018), sugarcane (Wang et al, 2021), and potato (Zhang et al, 2020). Thus, it will be interesting to study whether the homologues of SBP1 and SBP2 in other species are also involved in RLP‐mediated immune signaling.…”
Section: Discussionmentioning
confidence: 99%
“…FLS2 typically heterodimers with BAK1 and undergoes transphosphorylation. Overall, RLKs play critical roles in regulating both plant development and stress responses [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%